Effect size measurement in functional milk product marketing - Karmen Pažek; Črtomir Rozman; Jernej Turk; Darja Majkovič; Sebjan Hari; Matej Kolenko; Sašo Pamič; Jernej Prišenk (Mljekarstvo)
The paper presents the application possibility of “Effect size” and Cohen’s-d index in the case of introduction of new milk products on the market. The field and online survey were used to establish the potential interest of final consumers for new functional food product of dairy company in Slovenia - milk with phytosterols additives. Two techniques possibilities of Cohen-d index were calculated; manual and using the Cohen’s-d calculator. Further, the application is focused on two main questions in survey regarding observed problem: 1) Would you buy milk with phytosterols additives, which scientifically proven lowers concentration of cholesterol in blood? 2) Would you pay for it at a higher price? The sample includes 419 surveys, 150 surveys were conducted on field (control group) and 269 surveys were provided online (experimental group). The Cohen’s-d index (d) results show by using manual and Cohen’s-d calculator for both groups “small” effect (d=0.35, i.e. d=0.34 ), and “zero or near zero” effect (d=0.15, i.e.= 0.15) when deciding to buy new milk product.